1978
DOI: 10.1192/bjp.133.2.111
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Social Work Service for Self-Poisoning Patients

Abstract: Four hundred patients aged at least 17 who came to Casualty in one year after deliberately poisoning themselves were randomly assigned between an Experimental social work service (task-centered casework) and a Control (routine) follow-up service. 139 patients were excluded from the trial, most of whom were already in continuing psychiatric treatment. After one year there was no difference in the proportions of E and C patients who repeated self-poisoning (about 14 per cent), but significantly more of the exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
3

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(78 citation statements)
references
References 11 publications
1
74
0
3
Order By: Relevance
“…For information on the effectiveness of the remaining interventions not covered in this report the reader is instead referred to our review in the Cochrane Library. 13 A total of 29 trials were therefore included in the present review (Figure 1; Supplementary Document SD3), comprising 18 trials of cognitive behavioural-based psychotherapy (CBT), [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] three trials of dialectical behaviour therapy (DBT), [36][37][38] and four trials each of case management [39][40][41][42] and postcards. [43][44][45][46] (Insert Figure 1 about here)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For information on the effectiveness of the remaining interventions not covered in this report the reader is instead referred to our review in the Cochrane Library. 13 A total of 29 trials were therefore included in the present review (Figure 1; Supplementary Document SD3), comprising 18 trials of cognitive behavioural-based psychotherapy (CBT), [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] three trials of dialectical behaviour therapy (DBT), [36][37][38] and four trials each of case management [39][40][41][42] and postcards. [43][44][45][46] (Insert Figure 1 about here)…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Data on the proportion of patients repeating self-harm by the end of treatment was only available for one trial, 27 in which there was no apparent effect (23/171 vs. 27/142, OR 0路66, 95% CI 0路36 to 1路21, N=313). However, CBT-based therapy was associated with fewer participants repeating self-harm at the six month (OR 0路54, 95% CI 0路34 to 0路85, N=1,317; Figure 2) and 12 month follow-up assessments (OR 0路80, 95% CI 0路65 to 0路98, N=2,232; Figure 2).…”
Section: Cognitive Behavioural-based Psychotherapy Versus Treatment Amentioning
confidence: 99%
“…In three of the trials the descriptions of treatment were very similar (Patsiokas & Clum, 1985 ;Salkovskis et al 1990). In Gibbons et al (1978) the treatment (task-centred casework) focused on working on a single key problem. In McLeavey et al (1994) particular attention was paid to improving problem-solving skills in general as well as tackling current problems.…”
Section: Identification Of Relevant Trialsmentioning
confidence: 99%
“…These commonly include interpersonal difficulties (especi-ally with partners and family members), unemployment, financial and housing problems and social isolation (Paykel et al 1975 ;Gibbons et al 1978 ;Hawton et al 1997 ;Williams & Pollock, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have found that treatment by medical or non-medical personnel lasting around three months may lead to improvement in social adjustment (Chowdhury et al 1973;Hawton et al 1981), social problems (Gibbons et al 1978) or mood (Hawton et al 1981), but that no available at https://www.cambridge.org/core/terms. https://doi.org/10.1017/S0033291700038800 Downloaded from https://www.cambridge.org/core.…”
Section: From Prediction To Interventionmentioning
confidence: 99%